Sulfur-resistant and regenerable Ni/Co spinel-based catalysts for methane dry reforming. Issue 9 (17th September 2015) - Misture, S. T.; McDevitt, K. M.; Glass, K. C.; Edwards, D. D.; Howe, J. Y.; Rector, K. D.; He, H.; Vogel, S. C.
<x xml:space="preserve">Abstract</x> High-perfection Ni/Co spinel microcrystalline catalysts with extensive faceting show high turnover frequencies in methane dry reforming and good sulfur tolerance.